2020
DOI: 10.1590/s0102-865020200070000003
|View full text |Cite
|
Sign up to set email alerts
|

Use of thermography in skin grafts after the application of therapeutic ultrasound in Wistar rats

Abstract: Conception and design of the study; acquisition, analysis and interpretation of data; manuscript preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…After euthanasia, a “U"-shaped incision was made along the abdominal wall and the rate of implant adhesion to the viscera was evaluated according to Kist and coworkers [ 19 ] and classified into different degrees [ 20 ]: Grade 0 - absence of adhesions; Grade 1 - reduced number of adhesions (≤3), fibrinous and easily undone by manipulation without injuring the viscera; Grade 2 - firm adhesions (>3), resistant to manipulation between the abdominal wall and the organ; Grade 3 - firm adhesions, resistant to manipulation between intestinal loops but not involving the abdominal wall; Grade 4 - firm adhesions, resistant to manipulation between intestinal loops and between the loops and the abdominal wall with enteric fistula.…”
Section: Methodsmentioning
confidence: 99%
“…After euthanasia, a “U"-shaped incision was made along the abdominal wall and the rate of implant adhesion to the viscera was evaluated according to Kist and coworkers [ 19 ] and classified into different degrees [ 20 ]: Grade 0 - absence of adhesions; Grade 1 - reduced number of adhesions (≤3), fibrinous and easily undone by manipulation without injuring the viscera; Grade 2 - firm adhesions (>3), resistant to manipulation between the abdominal wall and the organ; Grade 3 - firm adhesions, resistant to manipulation between intestinal loops but not involving the abdominal wall; Grade 4 - firm adhesions, resistant to manipulation between intestinal loops and between the loops and the abdominal wall with enteric fistula.…”
Section: Methodsmentioning
confidence: 99%
“…In the treated group, the authors found higher temperatures between 35 and 36 °C, while the control group had lower values between 33.3 and 34.3 °C. This could be interpreted as an improved tissue repair using ultrasound [ 71 ]. In another study in mongrel dogs, Lekas et al [ 72 ] monitored coronary artery bypass grafting and found that thermal imaging can accurately identify ischemic processes due to stenosis or occlusion of the coronary artery.…”
Section: Thermal Imaging Applied To Assess Tissular Damage Degree And...mentioning
confidence: 99%